Endogenous and exogenous bone morphogenetic protein-2 play an important role in chondrocytic differentiation and maturation in rat cord blood-derived mesenchymal progenitor cells - UCHIDA, KENTARO; NARUSE, KOUJI; UENO, MASAKI; ONUMA, KENJI; URABE, KEN; SAKAI, RINA; MORIYA, MITSUTOSHI; ITOMAN, MORITOSHI; TAKASO, MASASHI (The Indian Journal of Animal Sciences, 2012)
Bone morphogenetic protein-2 (BMP-2) strongly induces chondrogenesis in the presence of transforming growth factor beta-1 (TGF-β1) or –3 in bone marrow (BM), synovium, adipose, and muscle-derived mesenchymal stem cells (MSCs). However, the effect of BMP-2 on umbilical cord derived (UCB)-derived MSCs, which are potentially useful for cartilage repair, has not been elucidated. In this study, the effect of endogenous and exogenous BMP-2 on rat umbilical cord blood-derived mesenchymal progenitor cells (UCB-MPCs) was evaluated. When cells were cultured in medium supplemented with only 10% FBS, type II procollagen (COL2A1) transcripts and collagen II protein were detectable after 2 weeks in UCB-MPCs, but not in BM-MPCs. The BMP antagonist, noggin, suppressed gene expression of COL2A1 and SOX-9 in UCB-MPCs. Exogenous BMP-2 promoted chondrogenic differentiation of UCB-MPCs in a dose-dependent manner, even in the absence of exogenous TGF-b1. UCB-MPCs expressed both type IIA and IIB procollagen in medium supplemented with only 10% FBS. Notably, exogenous BMP-2 was able to stimulate COL2A1 expression, particularly that of the type IIB transcripts, and also induce chondrogenic differentiation in rat UCB-MPCs. Interestingly, TGF-β1 inhibited BMP-2-induced COL2A1 splicing. As our results suggest that exogenous BMP-2 plays an important role for the spontaneous differentiation of chondrogenic lineages in rat UCB-MPCs, exogenous BMP-2 may effectively promote cartilage repair when UCB-MPCs are used.